2019
DOI: 10.1038/s41467-019-12939-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural water and disordered structure promote aqueous sodium-ion energy storage in sodium-birnessite

Abstract: Birnessite is a low-cost and environmentally friendly layered material for aqueous electrochemical energy storage; however, its storage capacity is poor due to its narrow potential window in aqueous electrolyte and low redox activity. Herein we report a sodium rich disordered birnessite (Na0.27MnO2) for aqueous sodium-ion electrochemical storage with a much-enhanced capacity and cycling life (83 mAh g−1 after 5000 cycles in full-cell). Neutron total scattering and in situ X-ray diffraction measurements show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 67 publications
2
81
1
Order By: Relevance
“…Several mechanisms for Na + -(de)intercalation into birnessite were already postulated. Most of them have in common, that they focus mainly on the variations of the d 001 -spacing which were explained by the (de)intercalation of Na-ions 5,17,28 or hydrated Na-ions 5 . In this regard, the current response in potential regions, where no variations in d 001 -spacing or changes in the Raman spectra were observed, were assigned to surface processes.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms for Na + -(de)intercalation into birnessite were already postulated. Most of them have in common, that they focus mainly on the variations of the d 001 -spacing which were explained by the (de)intercalation of Na-ions 5,17,28 or hydrated Na-ions 5 . In this regard, the current response in potential regions, where no variations in d 001 -spacing or changes in the Raman spectra were observed, were assigned to surface processes.…”
Section: )mentioning
confidence: 99%
“…Layered metal oxides are attractive cathode materials for sodium- [1][2][3][4][5] and potassium-ion [6][7][8] batteries and pseudocapacitors. One promising material belonging to this material class are birnessitetype manganese oxides which exhibits a theoretical capacity of 243mAhg -1 .…”
Section: Introductionmentioning
confidence: 99%
“…This partial solvation shell is known as frustrated water and has shown enhancements in electron transfer within catalyst materials. [20,99] While the structure/order of water in layered materials can be assessed through neutron diffraction/scattering studies, [100,101] distinct types of water (free vs bound water) can also be identified through thermogravimetric analysis (TGA) of the as-prepared zirconium phosphate catalyst powders. [57] In TGA measurements, the removal of weakly coordinated water (free water) is associated with the first dehydration event and is usually observed below 90-120 °C.…”
Section: Interlayer Environment Is Important For Catalytic Enhancementmentioning
confidence: 99%
“…[ 56 ] The co‐intercalation of water molecules and cations can significantly impact the performance of the resultant materials, as evidenced by Shan et al. [ 57 ] As shown in Figure 6g, the authors synthesized Na‐inserted birnessite (Na 0.27 MnO 2 ) using a solution‐phase method. Upon co‐intercalation of Na cations and water molecules, the sodium storage capability improved substantially.…”
Section: Applications Of Layered Materials In Energy Storage Devicesmentioning
confidence: 99%